Lithium nickel manganese oxide positive electrode material and preparation method thereof

By adopting a three-layer structure of core-middle-layer-outer layer on the nickel-manganate positive electrode material, the problem of reduced structural stability at high voltage is solved, cycling performance and rate performance are significantly improved, and corrosion resistance and safety are enhanced.

CN119890293AActive Publication Date: 2025-04-25SUZHOU AMIT MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510064228.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The spinel-type lithium nickel manganate positive electrode material is prone to react with the electrolyte at high voltage, resulting in reduced structural stability and deterioration of circulation performance, especially at high temperatures, hindering its commercialization process.

Method used

The three-layer structure of core-intermediate layer-the outermost layer is adopted. The core is lithium nickel manganate doped with Al, Ti, Mg, V, La, Zr, Sr, and Y. The intermediate layer is Li3PS4 generated in situ and doped with C. The outermost layer is a carbon network layer formed by hydrolysis and condensation of organosilane.

Benefits of technology

The circulation performance and rate performance of the positive electrode material are significantly improved, structural integrity and stability are enhanced, corrosion resistance and safety are improved, and the deterioration of high-temperature cycle performance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890293A_ABST
    Figure CN119890293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery positive electrode materials, in particular to a lithium nickel manganese oxide positive electrode material and a preparation method thereof.The lithium nickel manganese oxide positive electrode material comprises an inner core, a middle layer wrapping the outer surface of the inner core and a carbon network layer located on the outer surface of the middle layer, the chemical formula of the inner core is LiNix MnyTzO4, x is larger than or equal to 0.39 and smaller than or equal to 0.51, y is larger than or equal to 1.4 and smaller than or equal to 1.6, z is larger than or equal to 0.01 and smaller than or equal to 0.1, and x + y + z is smaller than or equal to 2, the element T is selected from one or more of Al, Ti, Mg, V, La, Zr, Sr and Y, and the middle layer is Li3PS4 which is generated in situ and doped with C; the carbon network layer is formed by sintering organosilane after hydrolysis and condensation, the three-layer structure generates positive synergistic effect, mutual influence and combined effect, and the cycle performance and the rate capability of the positive electrode material are finally improved; the preparation method is good in repeatability, can be used for mass production, and is beneficial to industrial production and commercial application of the lithium nickel manganese oxide positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery positive electrode materials, in particular to a lithium nickel manganese oxide positive electrode material and a preparation method thereof. Background Art

[0002] Spinel-type lithium nickel manganese oxide cathode material, referred to as LNMO, has a high discharge voltage platform, a theoretical capacity of up to 147 mAh / g, can provide a high battery energy density, and has good cycle stability and thermal stability. It is one of the potential cathode materials for lithium-ion batteries. However, under high voltage, LNMO easily reacts with the electrolyte, which increases the strain and stress of the cathode material lattice structure, increases the grain boundaries, and causes transition reduction of transition metal ions, thereby reducing the structural stability of the cathode material. Long-term charge and discharge cycles will deteriorate the battery's cycle performance, especially at high temperatures, where the degradation of the battery's cycle performance is aggravated, thus hindering the commercialization of LNMO.

[0003] Therefore, it is urgently needed to be improved. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a nickel-manganese-oxide lithium positive electrode material and a preparation method thereof.

[0005] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0006] On the one hand, the present invention provides a lithium nickel manganese oxide positive electrode material, comprising a core, an intermediate layer coated on the outer surface of the core, and a carbon network layer located on the outer surface of the intermediate layer;

[0007] The chemical formula of the core is LiNi x Mn y T z O4, wherein: 0.39≤x≤0.51, 1.4≤y≤1.6, 0.01≤z≤0.1, 1.87≤x+y+z≤2, and the T element is selected from one or more of Al, Ti, Mg, V, La, Zr, Sr, and Y;

[0008] The intermediate layer is Li3PS4 generated in situ and doped with C;

[0009] The carbon network layer is formed by sintering organic silane after hydrolysis and condensation.

[0010] In this embodiment, x can be 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.51, etc., and y can be 1.4, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.5, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 2. 5, 1.56, 1.57, 1.58, 1.59, 1.6, etc., z can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc., and x+y+z can be 1.87, 1.88, 1.89, 1.9, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, 2, etc.

[0011] The present invention uses lithium nickel manganese oxide doped with one or more of Al, Ti, Mg, V, La, Zr, Sr, and Y as the inner core, first generates C-doped Li3PS4 in situ on the outer surface of the inner core, and then coats the outer surface of Li3PS4 with a carbon network layer, forming a three-layer structure of inner core-middle layer-outermost layer; the in-situ formed middle layer Li3PS4 is doped with conductive C, which can not only significantly improve the ion conductivity and provide abundant lithium ion transmission channels, but also has strong electron transmission ability, so the cycle performance and rate performance can be significantly improved; the outermost carbon network layer, while further promoting the transfer of electrons between the lithium nickel manganese oxide positive electrode material and the electrolyte, reducing the internal resistance, and improving the battery charge and discharge efficiency, also plays a physical barrier role, effectively isolates the middle layer from moisture in the air, protects the surface of the middle layer from corrosion, and more importantly, it can also effectively prevent the middle layer of the positive electrode material from falling off during the battery cycle, thereby enhancing the structural integrity and stability of the positive electrode material; the three-layer structure produces a positive synergistic effect, influences each other, and acts together, ultimately improving the cycle performance and rate performance of the positive electrode material.

[0012] Preferably, the thickness of the intermediate layer is not more than 25nm, the thickness of the carbon network layer is 2-20nm, such as 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, etc., more preferably 5-12nm; the content of the carbon network layer is 0.5wt%-5wt%, such as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1 .6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt% etc., more preferably 2%-3%.

[0013] If the carbon network layer is too thick and the carbon content is too high, on the one hand, it will increase the cost and complexity, requiring more carbon sources, longer coating time and more difficult control process, and on the other hand, it will hinder the diffusion path of lithium ions, affect the removal and embedding of lithium ions, make the transmission of lithium ions difficult, and then affect the charge and discharge reaction of the battery, reducing the cycle stability and rate performance of the battery. The present invention has found through creative labor that when the thickness and content of the carbon network layer are within the above-mentioned limited range, the carbon network layer will not have a significant adverse effect on the diffusion performance of lithium ions while playing its own role, and the carbon network layer is easy to obtain, low cost, and the control process is relatively simple.

[0014] Preferably, the contact angle of the carbon network layer is ≥150°, and the rolling angle of the carbon network layer is <5°.

[0015] The outermost carbon network layer not only plays a conductive role and a physical barrier role, but also has hydrophobic properties. The present invention finds that the carbon network layer of the product obtained in the previous embodiment: its contact angle is ≥150°, that is, it exhibits super-hydrophobic characteristics, and the super-hydrophobic surface can effectively resist the penetration of moisture and corrosive substances, thereby improving the corrosion resistance of the lithium nickel manganese oxide positive electrode material; its rolling angle is <5°, and water droplets are very easy to move on the surface of the carbon network layer. The non-wettability and self-cleaning properties of the surface of the carbon network layer are good. When the carbon network layer is impacted by water droplets, it is very stable and is not easy to produce stress concentration or corrosion points due to the accumulation of water droplets. Therefore, the carbon network layer can more effectively resist the penetration of moisture and corrosive substances, thereby improving the corrosion resistance of the positive electrode material; at the same time, good self-cleaning properties also help to reduce the contact time between moisture and the positive electrode material, further reduce the risk of water corrosion, and help to significantly improve the cycle stability and safety of the battery.

[0016] Preferably, the D50, specific surface area a, and tap density b of the lithium nickel manganese oxide positive electrode material satisfy the following relationship: 4 μm<D50<6.5 μm, 0.6 μm 2 / g <a<1.5m 2 / g, 1.2g / cm 3 <b<2.0g / cm 3 .

[0017] Generally speaking, a smaller D50 is conducive to the diffusion of lithium ions, but it may cause the specific surface area of ​​the lithium nickel manganese oxide positive electrode material to be too large, increasing the side reaction with the electrolyte.

[0018] The specific surface area has a significant impact on the electrochemical performance. A larger specific surface area helps to improve the utilization rate of active materials and shorten the diffusion path of lithium ions inside the positive electrode material, thereby increasing the charge and discharge rate of the battery; however, too large a specific surface area may also lead to an increase in structural defects on the surface of the positive electrode material, affecting the material's cycle stability and safety.

[0019] For positive electrode materials, the size of the tap density is closely related to its specific capacity and the cycle performance of the battery. As the tap density of lithium nickel manganese oxide increases, the specific capacity of the positive electrode material will also increase. However, the increase in tap density will also have a certain negative impact on the cycle performance of the positive electrode material, especially under high-rate charge and discharge conditions, lithium nickel manganese oxide positive electrode materials with large tap density are prone to polarization, resulting in reduced battery performance. In addition, when the tap density is too large, the lithium nickel manganese oxide positive electrode material will generate a lot of heat during charging and discharging, which may cause safety accidents such as battery overheating, fire, and even explosion.

[0020] Therefore, the D50, specific surface area a, and tap density b of the lithium nickel manganese oxide positive electrode material need to be controlled within a reasonable range. The present invention has found through experiments that when the D50, a, and b of the product simultaneously meet the following conditions: 4μm<D50<6.5μm, 0.6μm 2 / g <a<1.5m 2 / g, 1.2g / cm 3 <b<2.0g / cm 3 When the electrochemical performance of the obtained lithium nickel manganese oxide positive electrode material is good.

[0021] On the other hand, the present invention provides a method for preparing a lithium nickel manganese oxide positive electrode material, comprising the following steps:

[0022] S1. Preparation of core material

[0023] The lithium source, nickel manganese hydroxide and T element doping source are first mixed uniformly according to the stoichiometric ratio shown in the chemical formula of the core, and then calcined at 700-1000° C. for 4-15 hours, preferably 8-14 hours, and then pulverized and sieved after cooling to obtain;

[0024] S2. Preparation of intermediate layer materials

[0025] First, a carbon source and a lithium sulfur source are uniformly mixed to form a carbon lithium sulfur precursor, and then the carbon lithium sulfur precursor is sintered at 600-1000° C. in an inert atmosphere for 4-8 hours;

[0026] S3. Forming an intermediate layer on the surface of the core material

[0027] First, the core material obtained in step S1, the intermediate layer material obtained in step S2 and a phosphorus source are uniformly mixed, and then the obtained mixture is heat-treated at 200-400° C. for 0.5-2 h;

[0028] S4, coated carbon network layer

[0029] First, the product obtained in step S3 and the organosilane are added to deionized water and stirred evenly, and then a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is added, and the stirring is continued to obtain a solid-liquid mixture, and then the solid-liquid mixture is filtered, washed, and dried, and finally sintered at 150-200° C. for 1-3 hours.

[0030] Need to explain:

[0031] In step S1, the core material is crushed and sieved, and the particle size after sieving is 2 μm-10 μm, and more preferably 4 μm-6.5 μm.

[0032] In step S2: the method for forming a carbon lithium sulfur precursor is a prior art, and a dry method such as ball milling can be used for uniform mixing, and a wet method can also be used for uniform mixing, such as first adding a sulfur source to deionized water and stirring evenly, and then adding a carbon source and a small amount of organic solvent (one or more of methanol, ethanol, cyclohexane, dimethylformamide, etc.), stirring evenly again, and drying at 100-200° C. to obtain a carbon lithium sulfur precursor. The inert atmosphere can be provided by an inert gas such as nitrogen, argon, helium, etc., and the ventilation rate of the inert gas during sintering is preferably 0.1-2L / min.

[0033] In step S3: the core material, the intermediate layer material and the phosphorus source are preferably mixed by dry mixing, that is, the three materials are mixed in proportion and placed in a ball mill for high-speed ball milling.

[0034] In step S4: the material obtained after filtration is washed with a mixture of anhydrous ethanol and deionized water, wherein the preferred mass ratio of the material, anhydrous ethanol and deionized water is 1:1:4, and after washing, the material is dried at 80° C. for 5-10 hours and then sintered.

[0035] The preparation method proposed in the present invention first prepares a core material and an intermediate layer material, then mixes the core material, the intermediate layer material and the phosphorus source evenly and sinters, forms an intermediate layer on the outer surface of the core material, and then coats the outer surface of the intermediate layer with a carbon network layer, and finally obtains the lithium nickel manganese oxide positive electrode material proposed in the present invention. This preparation method has good repeatability, is easy to operate, and can be mass-produced, which is helpful to realize the industrial production and commercial application of the lithium nickel manganese oxide positive electrode material.

[0036] Preferably, in step S1, the lithium source is selected from one or more of lithium acetate, lithium carbonate, lithium hydroxide, and lithium nitrate, and the T element doping source is selected from one or more of compounds containing Al, Ti, Mg, V, La, Zr, Sr, and Y such as acetates, carbonates, hydroxides, etc., and preferably, a compound that only contains the T element without introducing other impurity elements is used.

[0037] Preferably, in step S2, the carbon source is selected from one or more of glucose, sucrose, polyethylene glycol, acetylene black, carbon nanotubes, phenolic resin, and resorcinol-formaldehyde resin; the lithium sulfur source is selected from one or more of lithium germanium phosphorus sulfur, lithium phosphorus sulfur, and lithium sulfate, preferably a phosphorus-containing lithium sulfur source; and the mass ratio of the carbon source to the lithium sulfur source is 1:(0.3-0.75); in step S3, the phosphorus source is selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, and phosphorus sulfide; and the mass ratio of the core material, the intermediate layer material, and the phosphorus source is 1:(0.01-0.05):(0.01-0.03).

[0038] In this embodiment, the raw materials can form an intermediate layer Li3PS4 doped with an appropriate amount of conductive C in situ on the outer surface of the inner core according to the specified mass ratio, and the thickness of the intermediate layer does not exceed 25 nm.

[0039] Preferably, in step S4, the concentrated sulfuric acid is 90wt% sulfuric acid, the concentrated nitric acid is 75wt% nitric acid, and deionized water, 90wt% sulfuric acid, and 75wt% nitric acid are mixed in a mass ratio of 1:(0.25-0.3):(0.1-0.2); first, the product obtained in step S3 and the organosilane are added to deionized water and stirred for 1h, and then 90wt% sulfuric acid and 75wt% nitric acid are added, and stirred at room temperature for 5-12h, particularly preferably 8-10h, to obtain the solid-liquid mixture.

[0040] In this embodiment, the mixed acid solution is mixed with deionized water, 90wt% sulfuric acid, and 75wt% nitric acid in a mass ratio of 1: (0.25-0.3): (0.1-0.2). The mixed acid solution can carry out surface pickling and etching on the product obtained in step S3, while promoting the rupture of the C-Si bond in the organic silane adhered to its surface, and then hydrolyze and condense to form a siloxane bond, and then construct a complex organic silicon polymer structure and stably adhere to the outer surface of the intermediate layer, and generate the outermost carbon network layer after sintering. In addition to playing a conductive role and a physical shielding role, the existence of the carbon network layer is more importantly to effectively prevent the intermediate layer from falling off during the battery cycle of the positive electrode material, and enhance the structural integrity and stability of the positive electrode material. It is speculated that there is a chemical bond between the carbon network layer obtained by the above-mentioned preparation method and the intermediate layer, such as Si-C, CP, CS, carboxyl groups, etc., which helps to increase the inter-particle force, enhance the bonding strength between the layers, improve the stability of the long cycle of the positive electrode material, and extend the service life of the positive electrode material.

[0041] In this embodiment, the composition of the mixed acid is of great significance for the firm, uniform and stable coating of the carbon network layer on the surface of the intermediate layer. If the amount of concentrated sulfuric acid and concentrated nitric acid added exceeds the above range, it will cause excessive pickling and etching of the particle surface, affecting the structural strength of the product. If the amount of concentrated sulfuric acid and concentrated nitric acid added is too small, it will cause incomplete pickling and etching of the particle surface and incomplete carboxylation treatment, affecting the coating uniformity and stability of the carbon network layer.

[0042] Preferably, in step S4, in the solid-liquid mixture, the content of the product obtained in step S3 is 8wt%, and the content of the organosilane is 0.4wt%-0.8wt%.

[0043] In this embodiment, the raw materials are mixed according to the specified content, and a carbon network layer with a thickness of 2-20 nm can be formed on the outer surface of the intermediate layer Li3PS4, and the content of the carbon network layer is 0.5wt%-5wt%.

[0044] Preferably, the organosilane is selected from one or more of methylsilane, vinylsilane, aminosilane, and hydrogensilane, and the methylsilane is one or more of methylbutyltrichlorosilane, isopropoxytrimethylsilane, epoxypropyltrimethylsilane, and perfluorodecyltrimethylsilane.

[0045] In this embodiment, the organosilane is preferably methylsilane. Concentrated nitric acid is a strong oxidant, which can react with the methyl-containing silane to make it easier to hydrolyze, and then generate corresponding silanol and alcohol compounds, which can further undergo condensation reactions to generate siloxane bonds, and then construct a complex organosilicon polymer structure and stably adhere to the outer surface of the intermediate layer, and generate a carbon network layer after sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0047] Figure 1 This is the SEM image of the product obtained in Example 1.

[0048] Figure 2 This is the SEM image of the product obtained in Example 2. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0050] It should be noted that the technical means not described in detail below all adopt conventional technical means in the art. The testing means not described in detail below all adopt conventional testing means in the art. Those skilled in the art can use them in combination without creative work.

[0051] Example 1

[0052] A lithium nickel manganese oxide positive electrode material, comprising a core, an intermediate layer coated on the outer surface of the core, and a carbon network layer located on the outer surface of the intermediate layer; the chemical formula of the core is LiNi 0.48 Mn 1.5 T 0.02O4, wherein: the T element is a combination of Al, Mg, and Zr, the intermediate layer is in-situ generated and C-doped Li3PS4; and the carbon network layer is formed by sintering methylbutyltrichlorosilane after hydrolysis and condensation.

[0053] The preparation method is as follows:

[0054] S1. Preparation of core material

[0055] The lithium carbonate, nickel manganese hydroxide, aluminum oxide, magnesium oxide and zirconium oxide are first mixed uniformly according to the stoichiometric ratio shown in the chemical formula of the core, and then calcined at 850° C. for 10 hours. After cooling, the mixture is crushed and sieved to obtain a product with a particle size of 4 μm to 6.5 μm.

[0056] S2. Preparation of intermediate layer materials

[0057] First, lithium phosphorus sulfur is added to deionized water and stirred evenly, and then glucose and a small amount of methanol are added, and the mass ratio of glucose to lithium phosphorus sulfur is 1:0.52. After stirring evenly again, it is dried at 180° C. to obtain a carbon lithium sulfur precursor. Finally, the carbon lithium sulfur precursor is sintered at 800° C. in a nitrogen atmosphere for 6 hours, and the ventilation rate of the inert gas during sintering is 1.5 L / min;

[0058] S3. Forming an intermediate layer on the surface of the core material

[0059] First, the core material obtained in step S1, the intermediate layer material obtained in step S2 and lithium phosphate are placed in a high-speed ball mill in a mass ratio of 1:0.03:0.02 to be evenly mixed, and then the obtained mixture is heat-treated at 300° C. for 1.5 hours;

[0060] S4, coated carbon network layer

[0061] First, the product obtained in step S3 and methylbutyl trichlorosilane are added to deionized water and stirred evenly, and then 90wt% of concentrated sulfuric acid and 75wt% of concentrated nitric acid are added. Deionized water, 90wt% of sulfuric acid and 75wt% of nitric acid are mixed in a mass ratio of 1:0.28:0.15, and stirred at room temperature for 9h to obtain a solid-liquid mixture, in which the content of the product obtained in step S3 is 8wt%, and the content of the organosilane is 0.6wt%. Then, the solid-liquid mixture is filtered, and the material obtained after the filtration is washed with a mixed solution of anhydrous ethanol and deionized water. During the washing, the mass ratio of the material, anhydrous ethanol and deionized water is 1:1:4. After washing, it is dried at 80°C for 8h, and then sintered at 180°C for 2h.

[0062] Depend on Figure 1 It can be seen that the particle size distribution of the obtained product is relatively uniform and the surface is relatively smooth. After testing, the D50 of the obtained product is 5.5μm and the specific surface area is 1.0m2 / g, tap density is 1.8g / cm 3 ; The thickness of the intermediate layer is 18nm, the thickness of the carbon network layer is 10nm and the content of the carbon network layer is 2.5wt%, the contact angle of the carbon network layer is 155°, and the rolling angle of the carbon network layer is 4°.

[0063] Example 2

[0064] Compared with Example 1, methylbutyl trichlorosilane was adjusted to an equal amount of vinyl trimethoxysilane. The rest was the same as Example 1.

[0065] Depend on Figure 2 It can be seen that the particle size distribution of the obtained product is relatively uniform and the surface is relatively smooth. The appearance is not much different from that of the product of Example 1.

[0066] Example 3

[0067] Compared with Example 1, methylbutyl trichlorosilane was adjusted to an equal amount of γ-aminopropyl triethoxysilane. The rest was the same as Example 1.

[0068] Example 4

[0069] Compared with Example 1, methylbutyl trichlorosilane was adjusted to an equal amount of isopropoxy trimethylsilane. The rest was the same as Example 1.

[0070] Example 5

[0071] Compared with Example 1, methylbutyl trichlorosilane was adjusted to an equal amount of epoxypropyl trimethylsilane. The rest was the same as Example 1.

[0072] Example 6

[0073] Compared with Example 1, methylbutyl trichlorosilane was adjusted to an equal amount of perfluorodecyl trimethylsilane. The rest was the same as Example 1.

[0074] Example 7

[0075] Compared with Example 1, the chemical formula of the core is LiNi 0.46 Mn 1.4 T 0.1 O4, and the rest are consistent with Example 1.

[0076] Example 8

[0077] Compared with Example 1, the chemical formula of the core is LiNi 0.39 Mn 1.6 T 0.01 O4, and the rest are consistent with Example 1.

[0078] Example 9

[0079] Compared with Example 1, the chemical formula of the core is LiNi 0.4 Mn 1.42 T 0.05 O4, and the rest are consistent with Example 1.

[0080] Example 10

[0081] Compared with Example 1, the chemical formula of the core is LiNi 0.51 Mn 1.4 T 0.08 O4, and the rest are consistent with Example 1.

[0082] Embodiment 11

[0083] The positive electrode material of lithium nickel manganese oxide is the same as that of Example 1, but in step S4, deionized water, 90 wt% sulfuric acid, and 75 wt% nitric acid are mixed in a mass ratio of 1:0.25:0.2. The rest is the same as that of Example 1.

[0084] Example 12

[0085] The positive electrode material of lithium nickel manganese oxide is the same as that of Example 1, but in step S4, deionized water, 90 wt% sulfuric acid, and 75 wt% nitric acid are mixed in a mass ratio of 1:0.3:0.1. The rest is the same as that of Example 1.

[0086] Example 13

[0087] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but the mass ratio of glucose to lithium phosphorus sulfur in step S2 during preparation is 1:0.3. The rest is the same as Example 1.

[0088] Embodiment 14

[0089] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but the mass ratio of glucose to lithium phosphorus sulfur in step S2 during preparation is 1:0.75. The rest is the same as Example 1.

[0090] Embodiment 15

[0091] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but the mass ratio of the raw materials in step S3 is adjusted from 1:0.03:0.02 to 1:0.01:0.03 during preparation. The rest is the same as Example 1.

[0092] After testing, the D50 of the obtained product is 5.1μm and the specific surface area is 0.8m 2 / g, tap density is 1.8g / cm 3; The thickness of the intermediate layer is 15nm, the thickness of the carbon network layer is 10nm and the content of the carbon network layer is 3wt%, the contact angle of the carbon network layer is 154°, and the rolling angle of the carbon network layer is 3°.

[0093] Example 16

[0094] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but the mass ratio of the raw materials in step S3 is adjusted from 1:0.03:0.02 to 1:0.05:0.01 during preparation. The rest is the same as Example 1.

[0095] After testing, the D50 of the obtained product is 5.3μm and the specific surface area is 1.1m 2 / g, tap density is 1.8g / cm 3 ; The thickness of the intermediate layer is 21 nm, the thickness of the carbon network layer is 10 nm and the content of the carbon network layer is 2 wt %, the contact angle of the carbon network layer is 155°, and the rolling angle of the carbon network layer is 4°.

[0096] Embodiment 17

[0097] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but in the solid-liquid mixture in step S4 during preparation, the content of the product obtained in step S3 is 8wt%, and the content of the organosilane is 0.4wt%. The rest is the same as in Example 1.

[0098] After testing, the D50 of the obtained product is 5.6μm and the specific surface area is 1.3m 2 / g, tap density is 1.8g / cm 3 The thickness of the intermediate layer is 18 nm, the thickness of the carbon network layer is 5 nm and the content of the carbon network layer is 0.5 wt %, the contact angle of the carbon network layer is 150°, and the rolling angle of the carbon network layer is 4.5°.

[0099] Embodiment 18

[0100] Compared with Example 1, the composition of the lithium nickel manganese oxide positive electrode material is the same, but in the solid-liquid mixture in step S4 during preparation, the content of the product obtained in step S3 is 8wt%, and the content of the organosilane is 0.8wt%. The rest is the same as in Example 1.

[0101] After testing, the D50 of the obtained product is 5.5μm and the specific surface area is 1.3m 2 / g, tap density is 1.8g / cm 3; The thickness of the intermediate layer is 18nm, the thickness of the carbon network layer is 12nm and the content of the carbon network layer is 5wt%, the contact angle of the carbon network layer is 157°, and the rolling angle of the carbon network layer is 3°.

[0102] Comparative Example 1

[0103] Compared with Example 1, the nickel manganese oxide lithium positive electrode material only contains a core, and does not contain an intermediate layer and an outermost layer; the rest of the technical details are consistent with Example 1. Compared with Example 1, the preparation method is only adaptively adjusted.

[0104] Comparative Example 2

[0105] Compared with Example 1, the lithium nickel manganese oxide positive electrode material contains a core and an intermediate layer, but no carbon network layer is provided; the rest of the technical details are consistent with Example 1. Compared with Example 1, the preparation method thereof is only adaptively adjusted.

[0106] Comparative Example 3

[0107] Compared with Example 1, the lithium nickel manganese oxide positive electrode material does not have an intermediate layer, that is, a carbon network layer is provided on the outer surface of the inner core; the rest of the technical details are consistent with Example 1. Compared with Example 1, the preparation method is only adaptively adjusted.

[0108] Comparative Example 4

[0109] Compared with Example 1, the intermediate layer of the nickel manganese oxide positive electrode material is doped with C and not doped with P, that is, no phosphorus source is added in step S3 during preparation, and the other technical details are consistent with Example 1.

[0110] Comparative Example 5

[0111] Compared with Example 1, the intermediate layer of the nickel manganese oxide positive electrode material is not doped with P and C, that is, no carbon source is added in step S2 and no phosphorus source is added in step S3 during preparation. The other technical details are consistent with Example 1.

[0112] Comparative Example 6

[0113] The positive electrode material of lithium nickel manganese oxide is the same as that of Example 1, but in step S4, deionized water, 90 wt% sulfuric acid, and 75 wt% nitric acid are mixed in a mass ratio of 1:0.2:0.05. The rest is the same as that of Example 1.

[0114] Comparative Example 7

[0115] The positive electrode material of lithium nickel manganese oxide is the same as that of Example 1, but in step S4, deionized water, 90 wt% sulfuric acid, and 75 wt% nitric acid are mixed in a mass ratio of 1:0.4:0.3. The rest is the same as that of Example 1.

[0116] The products obtained in Examples 1 to 18 and Comparative Examples 1 to 7 were used as positive electrode materials to assemble button-type batteries. The first-cycle charge capacity and first-cycle discharge capacity were tested at a voltage range of 2.8-4.95 V and 0.1C / 0.1C. The capacity retention rate after 100 cycles at 45°C was tested at 1C / 1C. The test results are shown in Table 1 below.

[0117] Table 1

[0118]

[0119]

[0120] As shown in Table 1:

[0121] (1) By comparing the test results of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, it can be seen that: setting C-doped Li3PS4 or setting a carbon network layer on the surface of the inner core can improve the first efficiency and high-temperature cycle performance of the lithium battery to a certain extent, but the improvement effect is limited; however, by first setting C-doped Li3PS4 on the surface of the inner core and then setting a carbon network layer, the first efficiency and high-temperature cycle performance of the lithium battery are significantly improved. By comparing the test results of Example 1, Comparative Example 4, and Comparative Example 5, it can be seen that the simultaneous doping of C and P in the intermediate layer can more effectively improve the first efficiency and high-temperature cycle performance of the lithium battery than selectively doping or not doping.

[0122] Obviously, the simultaneous existence of these three-layer structures and the doping of C and P in the middle layer will produce a positive synergistic effect on the cycle performance and rate performance of the positive electrode material. Moreover, from the test results of Example 1 to Example 17, it can be seen that the nickel manganese oxide positive electrode materials obtained under the preparation conditions specified in the present invention all have good high-temperature cycle performance.

[0123] (2) By comparing the test results of Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6, it can be seen that: under the premise of the same other conditions, when the organosilane used to prepare the outermost carbon network layer is methylbutyl trichlorosilane, isopropoxy trimethylsilane, epoxypropyl trimethylsilane, and perfluorodecyl trimethylsilane, the first efficiency of the product after forming a lithium battery is 93.71%-94.06%, and the capacity retention rate after 100 cycles at 45°C is 94%; and when the organosilane is vinyltrimethoxysilane and γ-aminopropyl triethoxysilane, the first efficiency of the product after forming a lithium battery is about 91%, and the capacity retention rate after 100 cycles at 45°C is 92%-93%. Obviously, when the organosilane is a methyl-containing organosilane, the obtained carbon network layer has a better effect on improving the electrochemical performance of the positive electrode material.

[0124] (3) By comparing the test results of Example 1, Comparative Example 6, and Comparative Example 7, it can be seen that: for the nickel manganese oxide positive electrode material of the same composition, if the concentrated sulfuric acid and concentrated nitric acid in the mixed acid used during preparation are less than or greater than the amount specified in the present invention, it has little effect on the initial effect of the lithium battery, but will cause the high-temperature cycle performance of the lithium battery to deteriorate significantly. The reason for this is that if the amount of concentrated sulfuric acid and concentrated nitric acid added exceeds the above range, it will cause excessive pickling and etching of the particle surface, affecting the structural strength of the product, and then deteriorating the cycle performance. If the amount of concentrated sulfuric acid and concentrated nitric acid added is too little, it will cause incomplete pickling and etching of the particle surface, incomplete carboxylation treatment, affecting the coating uniformity and stability of the carbon network layer, and also causing deterioration of the cycle performance.

[0125] In summary: the present invention uses lithium nickel manganese oxide doped with one or more of Al, Ti, Mg, V, La, Zr, Sr, and Y as the core, first generates C-doped Li3PS4 in situ on the outer surface of the core, and then coats the outer surface of Li3PS4 with a carbon network layer. The three-layer structure of core-middle layer-outermost layer formed can produce a positive synergistic effect, ultimately improving the cycle performance and rate performance of the positive electrode material.

[0126] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A lithium nickel manganese oxide positive electrode material, characterized in that: It comprises an inner core, an intermediate layer covering the outer surface of the inner core, and a carbon network layer located on the outer surface of the intermediate layer; The chemical formula of the core is LiNi x Mn y T z O4, wherein: 0.39≤x≤0.51, 1.4≤y≤1.6, 0.01≤z≤0.1, 1.87≤x+y+z≤2, and the T element is selected from one or more of Al, Ti, Mg, V, La, Zr, Sr, and Y; The intermediate layer is Li3PS4 generated in situ and doped with C; The carbon network layer is formed by sintering organic silane after hydrolysis and condensation.

2. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that The thickness of the intermediate layer is not greater than 25 nm, the thickness of the carbon network layer is 2-20 nm, and the content of the carbon network layer is 0.5 wt %-5 wt %.

3. The lithium nickel manganese oxide positive electrode material according to claim 2, characterized in that: The contact angle of the carbon network layer is ≥150°, and the rolling angle of the carbon network layer is <5°.

4. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The D50, specific surface area a, and tap density b of the lithium nickel manganese oxide positive electrode material satisfy the following relationship: 4 μm<D50<6.5 μm, 0.6 μm 2 / g <a<1.5m 2 / g, 1.2g / cm 3 <b<2.0g / cm 3 .

5. A method for preparing the lithium nickel manganese oxide positive electrode material according to any one of claims 1 to 4, characterized in that: The steps are as follows: S1. Preparation of core material The lithium source, nickel manganese hydroxide and T element doping source are first mixed uniformly according to the stoichiometric ratio shown in the chemical formula of the core, and then calcined at 700-1000° C. for 4-15 hours, and then crushed and sieved after cooling to obtain; S2. Preparation of intermediate layer materials First, a carbon source and a lithium sulfur source are uniformly mixed to form a carbon lithium sulfur precursor, and then the carbon lithium sulfur precursor is sintered at 600-1000° C. in an inert atmosphere for 4-8 hours; S3. Forming an intermediate layer on the surface of the core material First, the core material obtained in step S1, the intermediate layer material obtained in step S2 and a phosphorus source are uniformly mixed, and then the obtained mixture is heat-treated at 200-400° C. for 0.5-2 h; S4, coated carbon network layer First, the product obtained in step S3 and the organosilane are added to deionized water and stirred evenly, and then a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is added, and the stirring is continued to obtain a solid-liquid mixture, and then the solid-liquid mixture is filtered, washed, and dried, and finally sintered at 150-200° C. for 1-3 hours.

6. The preparation method according to claim 5, characterized in that: In step S1, the lithium source is selected from one or more of lithium acetate, lithium carbonate, lithium hydroxide, and lithium nitrate, and the T element doping source is selected from one or more of compounds containing Al, Ti, Mg, V, La, Zr, Sr, and Y; In step S2, the carbon source is selected from one or more of glucose, sucrose, polyethylene glycol, acetylene black, carbon nanotubes, phenolic resin, and resorcinol-formaldehyde resin, and the lithium sulfur source is selected from one or more of lithium germanium phosphorus sulfur, lithium phosphorus sulfur, and lithium sulfate. The mass ratio of the carbon source to the lithium sulfur source is 1:(0.3-0.75).

7. The preparation method according to claim 6, characterized in that: In step S3, the phosphorus source is selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, and phosphorus sulfide, and the core material, the intermediate layer material and the phosphorus source are in a mass ratio of 1:(0.01-0.05):(0.01-0.03).

8. The preparation method according to claim 5, characterized in that: In step S4, the concentrated sulfuric acid is 90wt% sulfuric acid, the concentrated nitric acid is 75wt% nitric acid, and deionized water, 90wt% sulfuric acid, and 75wt% nitric acid are mixed in a mass ratio of 1:(0.25-0.3):(0.1-0.2); First, the product obtained in step S3 and the organosilane are added to deionized water and stirred for 1 hour, and then 90 wt % of sulfuric acid and 75 wt % of nitric acid are added, and the mixture is stirred at room temperature for 5-12 hours to obtain the solid-liquid mixture.

9. The preparation method according to claim 5, characterized in that: In step S4, in the solid-liquid mixture, the content of the product obtained in step S3 is 8wt%, and the content of the organosilane is 0.4wt%-0.8wt%.

10. The preparation method according to claim 5, characterized in that: In step S4, the organosilane is selected from one or more of methylsilane, vinylsilane, aminosilane, and hydrogensilane, and the methylsilane is one or more of methylbutyl trichlorosilane, isopropoxy trimethylsilane, epoxypropyl trimethylsilane, and perfluorodecyl trimethylsilane.

Citation Information

Patent Citations

  • Silica-coated carbon black, electrode composition in which same is used, electrode for secondary cell, and secondary cell

    CN107207876A

  • Composite coated positive electrode material and preparation method thereof

    CN113471411A

  • Nanometer positive electrode material and preparation method and application thereof

    CN117855455A

  • Composite active material, method for producing composite active material, and battery

    US20130316237A1